Climate Change Impacts and Strategies for Mitigation and Adaptation in Agriculture - Bruce A. McCarl; Chin-Hsien Yu; Witsanu Attavanich (Atmosphere, 2021)
Agriculture is highly vulnerable to climate change-induced shifts in means, variability and extremes [...]